Producción de pellets utilizando subproductos del café y maíz para su aprovechamiento calorífico en la generación de vapor - Loor Zambrano, Jandry Lenin (2023)
The objective of this research was to evaluate the calorific value of pellets made from coffee and corn byproducts for their use in steam generation; for which a simplex-centroid mixture design was used with three factors, factor A (coffee grounds), factor B (corn rachis) and factor C (corn stalk), obtaining 22 experimental runs; The variables under study were: humidity, density, ash, durability, combustion time, volatile matter, fixed carbon, and calorific value; a correlation analysis was carried out between the calorific value and the type of combustion of the samples, where it was found that treatment 18 composed entirely of coffee grounds, which with humidity of 10.3905% had a calorific value of 16.1187 MJ/Kg and a combustion time of 108 minutes; likewise, with the use of the Statgraphics Centurion 16.103 program, the optimal value of each of the variables studied was obtained; a cost-benefit analysis was carried out using as a reference the mixture in equal proportions of the three factors under study and their calorific value provided where the suggested sales cost per kg of pellets is $0.61, with a profit of $0.10. The research showed that the humidity of the pellet has a direct influence on the calorific value and combustion time of the solid biofuel, also that of the factors under study, the coffee grounds had the best influence on most of the variables studied.